Enhancing Czech Startup Ecosystem with Insights from Finland - Profotová, Martina (2025)
This master’s thesis examines how insights from the Finnish startup ecosystem can be used to strengthen the development of the startup environment in Czechia. The thesis compares the key characteristics of both ecosystems. It outlines the factors that shape their performance, including access to finance, innovation capacity and cooperation between public, private and academic actors. It also incorporates findings from eleven semi-structured interviews with Czech founders, investors and ecosystem representatives. The thesis identifies the main challenges of the Czech startup environment and proposes recommendations inspired by Finnish practices that could contribute to a more coordinated and competitive startup ecosystem in Czechia.